A multiwavelength study of the H ii region G347.600 + 00.211 and its effects on the surrounding medium. Issue 3 (27th October 2021) - Cárdenas, S B; Cichowolski, S; Suad, L A; Molina Lera, J A; Gamen, R; Rizzo, L
ABSTRACT: We present a multiwavelength investigation of the H ii region G347.600+00.211, located at a distance of 7.9 kpc. We analyse the gas and dust properties aiming to disentangle the origin of the region as well as its role in the formation of new stars. G347.600 + 00.211 is very conspicuous at 1420 MHz and infrared wavelengths, showing an incomplete shell-like structure with two distinct zones of very intense emission. The infrared bubble S8 is part of the shell structure. The spatial distribution of the molecular gas shows the presence of six clouds located around the ionized region and showing a good morphological correlation with the 8-μ m emission. Cold dust is coincident with the dense gas shown in the CO measurements. As for the origin of the region, we found that the massive cluster [DBS2003]179 and two Wolf–Rayet (WR) stars are located at the same distance than the ionized gas. Based on a stellar density analysis, we inferred that one of the WR stars, 1181-81L, is also a probable member of the cluster. Both the cluster and the WR stars are not only within the ring-like structure, but are also located near the two spots of very heightened emission, suggesting they may be responsible for this bright emission. Finally, as expanding H ii regions are hypothesized to trigger star formation, we used different infrared point source catalogues to search for young stellar object candidates (cYSOs). A total of 33 cYSOs and 4 CH ii regions were identified projected on to the photodissociation regions and molecular clouds.